Quelques notes sur l’assurance maritime - Roberge, Louis (Assurances)

(untitled) (HEC Montréal, 1981)
Marine insurance has its roots in the seventeenth century and is the main reason behind the creation of Lloyd's of London. Whilst at that early stage, underwriters were concerned only with particular average, general average, total loss and constructive total loss of ships and cargo, the development of international trade has imposed many changes in the industry. Indeed, nowadays, whilst the liability of the ship-owner must be covered (Protection and Indemnity insurance), the marine insurance markets offer a wide range of coverage which ex tends to all aspects of the life of a ship, e.g. from its building until it is ship-broken. But this does not prevent the business from being affected by the same problems than the rest of the industry: competition, market capacity, mega brokers. Canadian international traders should be aware of the fact that marine insurance is one item in their costs, whether they are buyers or sellers, and they should do their upmost to benefit from it.